Transfer laminate, method for manufacturing negative electrode for lithium secondary battery, negative electrode for lithium secondary battery, and lithium secondary battery comprising negative electrode
By forming a surface protective film on the lithium metal layer of the lithium secondary battery and controlling its surface color difference, the problem of the initial irreversible capacity of the silicon-based negative electrode active material in the lithium secondary battery is solved, the risk of the lithium transfer process is reduced, and the improvement of the increase of the risk of the lithium transfer process is improved. The cycle life and energy density of the battery.
Patent Information
- Application Number
- CN202380049750.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-22
- Publication Date
- 2025-02-11
AI Technical Summary
When manufacturing lithium secondary batteries using silicon-based negative electrode active materials, there is a problem of large initial irreversible capacity, which leads to a rapid decrease in battery capacity and cycle life. At the same time, the existing electrochemical prelithiation methods have the risk of ignition and explosion, and the production costs are high.
By defining the chromatic difference of lithium metal surface, the degree of oxidation reaction of lithium on the surface is determined, thereby achieving quantitative surface treatment of the transfer laminate. The method includes forming a surface protective film on the lithium metal layer to ensure that the color difference of the surface meets certain conditions to control the lithium transfer and prelithiation process.
It effectively reduces quality and stability problems during the lithium transfer process, reduces the risk of ignition and side reactions, and improves the cycle life and energy density of the battery.
Smart Images

Figure CN119422255A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a transfer laminate, a method for manufacturing a negative electrode for a lithium secondary battery, a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0182508 filed in the Korean Intellectual Property Office on December 23, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0003] As the use of fossil fuels is rapidly increasing, the demand for the use of alternative energy or clean energy is increasing, and as a part of this, the most active research field is the field of power generation and storage using electrochemical reactions.
[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to gradually expand.
[0005] With the technological development and increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased dramatically. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for manufacturing high-density electrodes with higher energy density per unit volume are being actively studied.
[0006] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and silicon-based particles having a high discharge capacity can be used as the negative electrode active material.
[0007] Generally, carbon materials such as graphite are used for the negative electrode of lithium secondary batteries, but the theoretical capacity density of carbon is 372 mAh / g (833 mAh / cm 3 ). Therefore, in order to improve the energy density of the negative electrode, silicon (Si), tin (Sn) and its oxides and their alloys (alloyed with lithium) are considered as negative electrode materials. Among them, silicon-based materials have attracted attention due to their low cost and high capacity (4200mAh / g).
[0008] However, in the case of using silicon-based negative electrode active materials, there is a problem of large initial irreversible capacity. That is, in the charge and discharge reaction of a lithium secondary battery, the lithium released from the positive electrode is embedded in the negative electrode during charging, and is deintercalated from the negative electrode during discharge and returns to the positive electrode again. In the case of silicon-based negative electrode active materials, the volume change and surface side reactions are severe, so a large amount of lithium embedded in the negative electrode during the initial charge will not return to the positive electrode again, so the initial irreversible capacity increases. When the initial irreversible capacity increases, there is a problem of rapid reduction in battery capacity and cycle.
[0009] In order to solve the above problems, a method for pre-lithiation of a silicon negative electrode containing a silicon-based negative electrode active material is known. As a pre-lithiation method, known methods include a method for manufacturing an electrode after lithiation by a physicochemical method such as electrolytic plating, lithium metal transfer and lithium metal deposition, and a method for electrochemically pre-lithiation of a negative electrode, etc.
[0010] In order to use the existing electrochemical method, a wet process should be performed in the electrolyte, which poses risks such as fire and explosion, so the inert environment must be well controlled. That is, when constructing the environment, it is difficult to control conditions such as moisture control by using an inert gas in the room where the electrochemical method is performed. In addition, in order to uniformly control the initial irreversible capacity, the rate of pre-lithiation should be slowed down as much as possible using the electrochemical method, so the problem that the production cost increases in the application of the electrochemical method.
[0011] In addition, there is a problem that during the pre-lithiation process, heat is generated in the process of inserting lithium into the electrode through the pressurization process. In particular, when the heating temperature of the electrode exceeds 30°C, lithium causes an oxidation reaction to promote side reactions, and there is also a risk of electrode ignition during the lithium transfer process. These risk factors are very important and should be controlled when performing the lithium transfer process.
[0012] In order to solve the heating phenomenon, the transfer laminate is subjected to appropriate surface treatment. However, there is no measurement method that can quantitatively confirm the extent to which the ignition stability and the suppression of the lithium oxidation reaction are effectively improved while enabling easy transfer. Therefore, the surface treatment is not properly performed, so that heating occurs and lithium oxidation is caused, resulting in side reactions, or the risk of electrode ignition cannot be avoided during the lithium transfer process.
[0013] Therefore, it is necessary to study standards that can quantify surface treatment.
[0014] [Prior art literature]
[0015] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0016] [Technical issues]
[0017] In order to solve the above problems, the inventors have confirmed that by defining the color difference of the lithium metal surface, the degree of oxidation reaction of lithium on the surface can be quantified, thereby solving the above problems.
[0018] Therefore, the present application relates to a transfer laminate, a method for manufacturing a negative electrode for a lithium secondary battery, a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.
[0019] [Technical solution]
[0020] An exemplary embodiment of the present specification provides a transfer laminate, the transfer laminate comprising a substrate layer and a lithium metal layer on one surface of the substrate layer, wherein the lithium metal layer comprises a surface protection film on the surface of the lithium metal layer, wherein the surface protection film comprises lithium carbonate (Li2CO3), and wherein the surface color difference for the surface of the lithium metal layer comprising the surface protection film satisfies the following formula (1):
[0021] L SCE ≥ 40 Formula (1)
[0022] In the above formula (1), L SCE Refers to the brightness index measured in the Specular Component Excluded (SCE) mode.
[0023] Another exemplary embodiment provides a method of manufacturing a negative electrode for a lithium secondary battery, the method comprising:
[0024] forming a negative electrode for a lithium secondary battery by forming a negative electrode collector layer and a negative electrode active material layer on one surface or both surfaces of the negative electrode collector layer; and
[0025] The lithium metal layer is transferred by laminating the transfer laminate according to the present specification onto the surface of the negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer.
[0026] In addition, an exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery manufactured by the method of manufacturing a negative electrode for a lithium secondary battery.
[0027] In addition, an exemplary embodiment of the present specification provides a lithium secondary battery including a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein one of the first electrode and the second electrode includes the negative electrode for the lithium secondary battery.
[0028] [Beneficial Effects]
[0029] The transfer laminate according to an exemplary embodiment of the present invention quantifies the degree of surface treatment as color difference, thereby defining the characteristics that enable the transfer process to be effectively performed, thereby making it easy to grasp the progress of the surface treatment process. By using the index of the surface treatment process, quality problems and stability problems that occur during the transfer process can be effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a view illustrating a process of transferring lithium metal to a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present specification.
[0031] Figure 2 is a view illustrating a stack structure of a lithium secondary battery according to an exemplary embodiment of the present specification.
[0032] <Description of Reference Numerals and Symbols>
[0033] 10: Base material layer
[0034] 20: Lithium metal layer
[0035] 30: Negative electrode active material layer
[0036] 40: Negative electrode collector layer
[0037] 55: Diaphragm
[0038] 60: Positive electrode collector layer
[0039] 70: Positive electrode active material layer
[0040] 100: Transfer laminate
[0041] 200: Negative electrode for lithium secondary battery
[0042] 300: Positive electrode for lithium secondary battery DETAILED DESCRIPTION
[0043] Before describing the present invention, some terms are first defined.
[0044] In the present specification, unless otherwise specifically described, when a part “includes,” “comprising,” or “has” a constituent element, this does not mean that another constituent element is excluded but means that another constituent element may be further included.
[0045] In this specification, “p to q” means a range of “p or more and q or less”.
[0046] In this specification, "specific surface area" is measured by the BET method, specifically, calculated by using BELSORP-mini II obtained from BEL Corporation of Japan based on the nitrogen adsorption amount at liquid nitrogen temperature (77K). That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.
[0047] In this specification, "Dn" means average particle size, and means the particle size at n% point according to the cumulative distribution of the number of particles of particle size. That is, D50 is the particle size at 50% point according to the cumulative distribution of the number of particles of particle size, D90 is the particle size at 90% point according to the cumulative distribution of the number of particles of particle size, and D10 is the particle size at 10% point according to the cumulative distribution of the number of particles of particle size. On the other hand, the average particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), wherein the difference in the diffraction pattern according to the particle size is measured when the laser beam passes through the particle, and then the particle size distribution is calculated.
[0048] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0049] <Transfer Laminate>
[0050] An exemplary embodiment of the present specification provides a transfer laminate, the transfer laminate comprising a substrate layer and a lithium metal layer on one surface of the substrate layer, wherein the lithium metal layer comprises a surface protection film on the surface of the lithium metal layer, wherein the surface protection film comprises lithium carbonate (Li2CO3), and wherein the surface color difference for the surface of the lithium metal layer comprising the surface protection film satisfies the following formula (1):
[0051] L SCE ≥ 40 Formula (1)
[0052] In the above formula (1), L SCE Refers to the brightness index measured in the specular component excluded (SCE, specular light excluded) mode.
[0053] In another exemplary embodiment of the present specification, in the surface color difference for the surface of the lithium metal layer including the surface protection film, L SCE The value of may be about 40 or more, preferably about 41 or more, more preferably about 42 or more, and about 100 or less, about 95 or less, about 90 or less, preferably 85 or less, or more preferably about 83 or less.
[0054] In the present specification, the surface color difference may be measured using an apparatus known in the art, and specifically, CM-2600d obtained from Konica Minolta may be used.
[0055] According to the above exemplary embodiment, the hardness of the surface of the lithium metal layer including the surface protection film can be grasped by defining the surface color difference as a brightness index measured in the SCE mode, wherein the brightness index defines the brightness of reflected light (mainly scattered light) excluding specular reflected light.
[0056] The transfer laminate according to the above exemplary embodiment may suppress ignition or side reaction due to heat generation by having a surface color difference within a specific range.
[0057] In the present specification, conditions for measuring the surface color difference of the lithium metal layer may include using a D65 standard light source, a field of view of 10°, and 100% UV.
[0058] In this specification, the surface treatment can be performed using carbon dioxide (CO2), but is not limited thereto. For example, the surface treatment can be performed using a single gas carbon dioxide (CO2) or a mixed gas of carbon dioxide and an inert gas (e.g., nitrogen (N2), argon (Ar), etc.).
[0059] In the present specification, a mixed gas of an inert gas (eg, argon gas) and carbon dioxide may be used, and a mixing ratio of argon gas to carbon dioxide may be 8:2, but is not limited thereto.
[0060] In the present specification, when the surface treatment is performed with a single gas of carbon dioxide (CO 2 ), lithium carbonate (Li 2 CO 3 ) as a lithium oxide may be included on the surface of the lithium metal layer as a main component.
[0061] In the transfer laminate according to the above exemplary embodiment, the color difference is defined for the surface of the lithium metal layer containing lithium carbonate (the lithium carbonate is lithium oxide), so that the surface treatment state that can improve stability in the future lithium transfer process can be grasped in a numerical form.
[0062] In an exemplary embodiment of the present specification, one or more components selected from the group consisting of LiOH, Li3N, Li2O, Li2O2, and combinations thereof may be further included on the surface of the lithium metal layer.
[0063] In the present specification, in the surface treatment process, when the lithium metal layer is surface-treated by exposure to oxygen, nitrogen, moisture, etc. in the atmosphere, lithium oxide (e.g., Li2O, Li2O2), lithium nitride (Li3N), lithium hydroxide (LiOH), etc. may be further included on the surface of the lithium metal layer as additional components.
[0064] In an exemplary embodiment of the present specification, the transfer laminate is provided, wherein the surface color difference for the surface of the lithium metal layer including the surface protection film satisfies the following formula (2):
[0065] L SCI ≥ 90 Formula (2)
[0066] In the above formula (2), L SCI Refers to the brightness index measured in the specular component (SCI, including specular reflected light) mode.
[0067] In another exemplary embodiment of the present specification, in the surface color difference for the surface of the lithium metal layer including the surface protection film, L SCI The value of may be about 80 or more, preferably about 85 or more, more preferably about 90 or more, and may be about 100 or less, preferably about 98 or less, more preferably about 96 or less.
[0068] In the transfer laminate according to the above exemplary embodiment, the color difference is defined for the surface of the lithium metal layer containing lithium carbonate (the lithium carbonate is lithium oxide), so that the surface treatment state that can improve stability in the future lithium transfer process can be grasped in a numerical form.
[0069] In another exemplary embodiment of the present specification, the surface color difference for the surface of the lithium metal layer including the surface protection film may satisfy both of the above formula (1) and formula (2).
[0070] In the transfer laminate according to the above exemplary embodiment, the color difference is defined for the surface of the lithium metal layer containing lithium carbonate (the lithium carbonate is lithium oxide), so that the surface treatment state that can improve stability in the future lithium transfer process can be grasped in a numerical form.
[0071] In the present specification, the surface color difference of the lithium metal layer may be measured using an apparatus known in the art, and specifically, CM-2600d obtained from Konica Minolta, Inc. may be used.
[0072] In an exemplary embodiment of the present specification, the thickness of the substrate layer may be 5 μm or more and 300 μm or less, preferably 10 μm or more and 100 μm or less. If the thickness of the substrate layer is less than 5 μm, process problems such as wrinkles and tears may occur during the process, and if the thickness exceeds 300 μm, it is difficult to increase the deposition rate because it is difficult to effectively remove heat during lithium deposition, which may lead to an increase in cost, etc.
[0073] In an exemplary embodiment of the present specification, the substrate layer may be one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate.
[0074] In an exemplary embodiment of the present specification, the thickness of the lithium metal layer may be 1 μm or more and 10 μm or less.
[0075] In another exemplary embodiment of the present application, the thickness of the lithium metal layer may be about 1 μm or more, about 2 μm or more, or about 3 μm or more, and about 10 μm or less, about 9 μm or less, or about 8 μm or less.
[0076] The thickness of the lithium metal layer satisfies the above range, so that the transfer of lithium metal to the negative electrode active material layer can occur effectively, reverse transfer can be prevented, and the negative electrode active material layer can be pre-lithiated to a desired degree.
[0077] In an exemplary embodiment of the present specification, a release layer may be further included between the substrate layer and the lithium metal layer.
[0078] In the transfer laminate according to the above exemplary embodiment, the substrate layer, the release layer (which may be referred to as a first release layer or a peeling layer) and the lithium metal layer are stacked in a corresponding order, wherein the release layer is used as a peeling layer for transferring lithium. The release layer makes it possible to prevent the reverse peeling problem of lithium metal being transferred to the substrate layer during the winding process for transferring the deposited lithium metal layer to the negative electrode, and also makes it possible to easily separate the substrate layer after transferring the lithium metal to the negative electrode active material layer.
[0079] In another exemplary embodiment of the present application, a release layer may be formed on both surfaces of the base material layer.
[0080] According to the above exemplary embodiment, the transfer laminate may further include a second release layer (which may also be referred to as a non-peeling layer) on the surface of the substrate layer opposite to the surface contacting the first release layer, based on the first release layer inserted between the substrate layer and the lithium metal layer.
[0081] The second release layer is an auxiliary structure for reducing friction with a roll during a roll-to-roll process.
[0082] In the present specification, the release layer may include one or more substances selected from the group consisting of silicon-modified polyester in which a silicon chain is grafted to a polyester main chain, an acrylic resin, Si, melamine, and fluorine.
[0083] In an exemplary embodiment of the present specification, the release layer may be formed by a coating method. For example, the coating method may be a method selected from the group consisting of dip coating, spray coating, spin coating, die coating, gravure coating, micro gravure coating, comma coating, inkjet coating, rod coating, wire rod coating, and roller coating, but is not limited thereto. That is, various coating methods that can be used to form a coating layer in the art may be used.
[0084] In an exemplary embodiment of the present specification, the thickness of the release layer may be 0.1 μm or more and 10 μm or less.
[0085] Preferably, the thickness of the release layer may be about 0.1 μm or more, about 0.2 μm or more, about 0.3 μm or more, about 0.4 μm or more, or about 0.5 μm or more, or about 10 μm or less, about 9.9 μm or less, about 9.8 μm or less, about 9.7 μm or less, or about 9.6 μm or less.
[0086] In the following lithium metal transfer process, the release layer is transferred onto the negative electrode active material layer together with the lithium metal layer. When the thickness of the release layer meets the above range, the coating uniformity of the release layer can be increased. In addition, when the above thickness range is met, the problem of increased battery resistance will not be caused.
[0087] <Method for manufacturing negative electrode for lithium secondary battery>
[0088] An exemplary embodiment of the present specification provides a method for manufacturing a negative electrode for a lithium secondary battery, the method including:
[0089] preparing a negative electrode for a lithium secondary battery by forming a negative electrode collector layer and a negative electrode active material layer on one surface or both surfaces of the negative electrode collector layer; and
[0090] The lithium metal layer is transferred by laminating the above transfer laminate onto the surface of the negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer.
[0091] In the present specification, the step of forming a negative electrode active material layer on one surface or both surfaces of a negative electrode collector layer includes coating a negative electrode slurry containing a negative electrode active material layer composition on one surface or both surfaces of the negative electrode collector layer, and the negative electrode active material layer composition may contain one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material and a negative electrode binder.
[0092] In an exemplary embodiment of the present specification, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.
[0093] In an exemplary embodiment of the present specification, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive.
[0094] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.
[0095] The solid content of the negative electrode slurry may refer to the content of the negative electrode active material layer composition included in the negative electrode slurry, and may refer to the content of the negative electrode active material composition based on 100 parts by weight of the negative electrode slurry.
[0096] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, so that particle aggregation of the negative electrode active material layer composition is minimized to effectively form the negative electrode active material layer.
[0097] In an exemplary embodiment of the present specification, the slurry solvent is not limited thereto as long as it can dissolve the negative electrode active material layer composition, but specifically, acetone, distilled water, or NMP may be used.
[0098] The negative electrode according to an exemplary embodiment of the present specification may be formed by coating the negative electrode slurry on the negative electrode collector layer and drying it.
[0099] Through the drying step, the slurry solvent in the negative electrode slurry can be dried, and then an electrode rolling step can be further included.
[0100] In an exemplary embodiment of the present specification, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel whose respective surfaces are treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, the negative electrode current collector layer may have fine irregularities formed on the surface to enhance the adhesion to the negative electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam body or non-woven fabric body.
[0101] An exemplary embodiment of the present specification includes a negative electrode active material layer formed on one surface or both surfaces of the negative electrode current collector layer and containing a negative electrode active material layer composition.
[0102] In an exemplary embodiment of the present specification, the negative electrode active material layer composition may include a silicon-based active material; a negative electrode conductive material; and a negative electrode binder.
[0103] In an exemplary embodiment of the present specification, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, metal impurities, and Si alloys.
[0104] In an exemplary embodiment of the present specification, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more.
[0105] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0106] In an exemplary embodiment of the present specification, for the silicon-based active material, pure silicon (Si) may be particularly used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that based on a total of 100 parts by weight of the silicon-based active material as described above, the content of pure Si particles (SiOx (x = 0)) not combined with other particles or elements is within the above range.
[0107] The capacity of the silicon-based active material is significantly higher than that of the commonly used graphite-based active material, so there have been more attempts to apply the silicon-based active material. However, the volume expansion rate of the silicon-based active material is high during charge and discharge, so that, for example, only a small amount of it is mixed with a graphite-based active material and used. In addition, despite the above advantages, the initial irreversible capacity is large and the life is shortened. In order to solve these problems, a pre-lithiation process of pre-lithiating the negative electrode is performed.
[0108] Therefore, according to the present invention, the main purpose of the present invention is to provide a transfer laminate, which enables the lithium metal layer to be transferred more smoothly to the negative electrode active material layer while only using a high content of silicon-based active material as the negative electrode active material to improve the capacity performance to solve the above-mentioned problems.
[0109] Note that the average particle size (D50) of the silicon-based active material of the present invention can be 5μm to 10μm, specifically 5.5μm to 8μm, and more specifically 6μm to 7μm. When the average particle size is within the above range, the specific surface area of the particles is within a suitable range, so that the viscosity of the negative electrode slurry is formed within an appropriate range. As a result, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the value of the size of the silicon-based active material is equal to or greater than the lower limit of the range, the contact area between the silicon particles and the conductive material is excellent due to the composite composed of the conductive material and the binder in the negative electrode slurry, thereby increasing the possibility of continuity of the conductive network and resulting in an increase in the capacity retention rate. Note that when the average particle size satisfies the above range, excessively large silicon particles are excluded, so that the negative electrode surface is formed smoothly. As a result, the current density non-uniformity during charge and discharge can be prevented.
[0110] In an exemplary embodiment of the present specification, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 to 150.0 m 2 / g, more preferably 0.1 to 100.0 m 2 / g, particularly preferably 0.2 to 80.0 m 2 / g, most preferably 0.2 to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0111] In an exemplary embodiment of the present specification, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure, or be present in the form of a silicon-containing film or coating.
[0112] In an exemplary embodiment of the present specification, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
[0113] In another exemplary embodiment, based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.
[0114] The negative electrode active material layer composition according to the present application uses a conductive material and a binder that can control the volume expansion rate during charge and discharge even when a silicon-based negative electrode active material having a significantly high capacity within the above range is used. Therefore, even when the silicon-based active material is within the above range, the negative electrode active material layer composition does not reduce the performance of the negative electrode and has excellent output characteristics during charge and discharge.
[0115] In the prior art, only graphite compounds are generally used as negative electrode active materials. However, in recent years, with the increasing demand for high-capacity batteries, attempts to mix and use silicon-based compounds have increased in order to increase capacity. However, silicon-based compounds are limited in that their volume expands rapidly during charge and discharge, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby reducing battery performance.
[0116] Therefore, in an exemplary embodiment of the present specification, the negative electrode conductive material may include one or more selected from the group consisting of a dot-shaped conductive material, a line-shaped conductive material, and a planar conductive material.
[0117] In an exemplary embodiment of the present specification, the dot-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode and has conductivity without causing chemical changes. Specifically, the dot-shaped conductive material can be one or more substances selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and in terms of high conductivity and excellent dispersibility, carbon black may be preferably included.
[0118] In an exemplary embodiment of the present specification, the BET specific surface area of the dot-shaped conductive material may be 40 m 2 / g or more and 70m 2 / g or less, preferably 45m 2 / g or above and 65m 2 / g or less, more preferably 50m2 / g or more and 60m 2 / g or less.
[0119] In an exemplary embodiment of the present specification, the particle diameter of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0120] In an exemplary embodiment of the present specification, the conductive material may include a planar conductive material.
[0121] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode while suppressing disconnection of a conductive path due to volume expansion, and can be expressed as a plate-shaped conductive material or a bulk-type conductive material.
[0122] In an exemplary embodiment of the present specification, the planar conductive material may include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0123] In an exemplary embodiment of the present specification, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size results in easy dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when dispersed using the same equipment and time, the dispersion effect is excellent.
[0124] In an exemplary embodiment of the present specification, a negative electrode composition is provided, wherein D10 of the planar conductive material is 0.5 μm or more and 1.5 μm or less, D50 is 2.5 μm or more and 3.5 μm or less, and D90 is 7.0 μm or more and 15.0 μm or less.
[0125] In an exemplary embodiment of the present specification, as the planar conductive material, a planar conductive material having a high specific surface area in which a BET specific surface area is high or a planar conductive material having a low specific surface area may be used.
[0126] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without restriction. However, in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersion effect in terms of electrode performance, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause dispersion problems.
[0127] In an exemplary embodiment of the present specification, the BET specific surface area of the planar conductive material may be 5 m 2 / g or above.
[0128] In another exemplary embodiment, the BET specific surface area of the planar conductive material may be 5 m 2 / g and above and 500m 2 / g or less, preferably 5m 2 / g and above and 300m 2 / g or less, more preferably 5m 2 / g and above and 250m 2 / g or less.
[0129] In another exemplary embodiment, the planar conductive material is a planar conductive material having a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above and 500m 2 / g or less, preferably 80m 2 / g and above and 300m 2 / g or less, more preferably 100m 2 / g and above and 300m 2 / g or less.
[0130] In another exemplary embodiment, the planar conductive material is a planar conductive material having a low specific surface area, and the BET specific surface area may satisfy 5 m 2 / g or more and 40m 2 / g or less, preferably 5m 2 / g or more and 30m 2 / g or less, more preferably 5m 2 / g or more and 25m 2 / g or less.
[0131] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a secondary shape of a bundle or rope in which a plurality of carbon nanotube units are aligned side by side or entangled in an orientation in which the longitudinal axes of the carbon nanotube units are substantially the same. The carbon nanotube units have graphene sheets and have sp 2 The graphite sheet has a cylindrical shape with a nanometer-scale diameter. In this case, the graphite sheet can exhibit the characteristics of a conductor or a semiconductor according to the rolling angle and structure of the graphite sheet. Compared with the entangled carbon nanotubes, the bundle-type carbon nanotubes can be more uniformly dispersed during the manufacture of the negative electrode and can more smoothly form a conductive network in the negative electrode to improve the conductivity of the negative electrode.
[0132] In an exemplary embodiment of the present specification, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0133] In another exemplary embodiment, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0134] The negative electrode conductive material according to the present application has a completely different structure from the conductive material used for the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active materials (the volume expansion of the electrode caused by charging and discharging is very large), while the positive electrode conductive material is used to impart a certain conductivity and play a buffering role during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of structure and function.
[0135] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material has only particles smaller than the active material, the conductive material is characterized by improving the output characteristics and imparting a certain conductivity, which is completely different from the negative electrode conductive material applied with the silicon-based active material as in the present invention in terms of structure and function.
[0136] In an exemplary embodiment of the present specification, the planar conductive material used as the above-mentioned negative electrode conductive material has a different structure and function from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot shape and used to promote the storage and release of lithium ions.
[0137] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate shape, and can be expressed as plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain the conductive path in the negative electrode active material layer, and refers to a material for ensuring a planar conductive path inside the negative electrode active material layer rather than a material for storing and releasing lithium.
[0138] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a plane or plate shape and using it as a material for ensuring a conductive path rather than for storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for storing and releasing lithium, and is used to store and release all lithium ions transferred from the positive electrode.
[0139] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot shape or a spherical shape and used as a material for storing or releasing lithium.
[0140] That is, in one exemplary embodiment of the present specification, the BET specific surface area of artificial graphite or natural graphite as a carbon-based active material may satisfy 0.1 m 2 / g or more and 4.5m 2 In addition, the plate-like graphite as a planar conductive material has a planar shape, and its BET specific surface area can be 5m 2 / g or above.
[0141] In an exemplary embodiment of the present specification, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above-mentioned materials whose hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0142] The negative electrode binder according to an exemplary embodiment of the present specification is used to hold the active material and the conductive material to prevent distortion and structural deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material. When such a role is met, all general binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.
[0143] In an exemplary embodiment of the present application, a method for manufacturing a negative electrode for a lithium secondary battery is provided, wherein the step of transferring the lithium metal layer by laminating the transfer laminate onto the surface of the negative electrode active material layer opposite to the surface in contact with the negative electrode collector layer includes laminating the transfer laminate so that the surface of the lithium metal layer opposite to the surface in contact with the substrate layer contacts the surface of the negative electrode active material layer opposite to the surface in contact with the negative electrode collector layer, and removing the substrate layer.
[0144] Figure 1 A method for manufacturing a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present specification is shown. Specifically, the following process is shown, wherein a transfer laminate 100 including a substrate layer 10 and a lithium metal layer 20 is prepared, the transfer laminate 100 is laminated so that the lithium metal layer 20 is in contact with a negative electrode active material layer 30 of the negative electrode 100 for a lithium secondary battery (wherein the negative electrode active material layer 30 is formed on a negative electrode collector layer 40), and then the substrate layer 10 is removed to transfer only the lithium metal layer 20 to the negative electrode active material layer 30.
[0145] In particular, as described above, since the step of transferring the lithium metal layer via the transfer laminate including the specific substrate layer according to the present application is included, the lithium metal layer can be transferred more easily.
[0146] In an exemplary embodiment of the present specification, there is provided a method of manufacturing a negative electrode for a lithium secondary battery, wherein the lamination is performed under a load of 200 kgf.
[0147] The lamination can be performed using a transfer process by calendering. Afterwards, a process of removing the substrate layer is included. During the removal, since the release layer according to the present application is included, direct contact between the lithium metal layer and the air can be prevented to protect the lithium metal layer. In addition, since the release layer is provided, the substrate layer can be easily removed even under weak linear pressure, so the pre-lithiation speed can be easily adjusted. In addition, since the substrate layer is removed, the heat generated during the pre-lithiation can be easily dissipated, thereby suppressing the generation of by-products.
[0148] In the present specification, the step of pre-lithiation of the negative electrode active material layer after the lithium metal layer is transferred may also be included. In this case, the pre-lithiation may be performed while the lithium metal layer is transferred onto the negative electrode active material layer, and it can be confirmed that the pre-lithiation has been completed when the lithium metal layer is completely removed as seen with the naked eye.
[0149] In an exemplary embodiment of the present specification, a method for manufacturing a negative electrode for a lithium secondary battery is provided, which also includes a step of pre-lithiating the negative electrode active material layer after transferring the lithium metal layer, and wherein in the step of pre-lithiating the negative electrode active material layer, the negative electrode active material layer is pre-lithiated within 30 minutes to 48 hours after transferring the lithium metal.
[0150] As described above, the substrate layer can be removed immediately after the lithium metal layer is transferred, and the removal of the substrate layer is easy to perform, thereby easily dissipating heat during the pre-lithiation period in which the lithium metal layer reacts with the negative electrode active material layer, resulting in less generation of by-products and uniform pre-lithiation in the negative electrode active material layer.
[0151] The completion time of the pre-lithiation can be calculated by measuring a period of time from the time when the lithium metal is transferred to the time when the transferred lithium metal is no longer observed on the surface of the negative electrode active material layer.
[0152] <Negative electrode for lithium secondary battery>
[0153] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery being manufactured by the method for manufacturing a negative electrode for a lithium secondary battery. The above description can be applied to the negative electrode of the exemplary embodiment of the present invention.
[0154] <Lithium Secondary Battery>
[0155] An exemplary embodiment of the present specification provides a lithium secondary battery including a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein one of the first electrode and the second electrode includes the above-mentioned negative electrode for a lithium secondary battery.
[0156] In the present specification, the first electrode may be a positive electrode, and the second electrode may be a negative electrode; or the first electrode may be a negative electrode, and the second electrode may be a positive electrode.
[0157] In the present specification, the positive electrode may include a positive electrode collector layer and a positive electrode active material layer formed on the positive electrode collector layer and including a positive electrode active material.
[0158] In the positive electrode, the positive electrode collector layer is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc. on each surface, etc. can be used. In addition, the positive electrode collector layer can typically have a thickness of 3 to 500 μm, and the surface of the positive electrode collector layer can be formed with fine concave and convex to enhance adhesion with the positive electrode active material. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0159] The positive electrode active material may be a typically used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, with the chemical formula LiNi 1-c2 M c2 O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4, wherein a portion of Li in the chemical formula is replaced by an alkaline earth metal ion; etc., but is not limited thereto. The positive electrode may be Li metal.
[0160] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.
[0161] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as it does not cause chemical changes in the battery to be constructed and has electronic conductivity. Specific examples may include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof may be used.
[0162] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.
[0163] The separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions, wherein any separator can be used as the separator without specific restrictions, as long as it is generally used for secondary batteries, in particular, it is preferred to use a separator with high moisture retention capacity for electrolytes and low resistance to the movement of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers; or a laminated structure having two or more layers thereof. In addition, a common porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be selectively used.
[0164] Figure 21 is a view showing a stack structure of a lithium secondary battery according to an exemplary embodiment of the present specification. Specifically, a negative electrode 100 for a lithium secondary battery can be seen, which includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10, a positive electrode 300 for a lithium secondary battery can be seen, which includes a positive electrode active material layer 70 on one surface of a positive electrode collector layer 60, and the negative electrode 100 for a lithium secondary battery and the positive electrode 300 for a lithium secondary battery form a stack structure together with a separator 55 interposed therebetween.
[0165] In this case, the release layer transferred together during the pre-lithiation may be partially removed depending on the electrolyte used, and thus, a small amount thereof is contained in the upper portion of the negative electrode. Figure 2 The release layer is not shown in the figure, but the release layer may be interposed between the substrate layer 10 and the lithium metal layer 20.
[0166] In an exemplary embodiment of the present specification, the electrolyte may be, but is not limited to, an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used to manufacture a lithium secondary battery.
[0167] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0168] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethyl ether, methyl propionate or ethyl propionate can be used.
[0169] Especially, among carbonate-based organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and because they have high dielectric constant to dissociate lithium salts well, they can be preferably used. When cyclic carbonate is mixed with linear carbonates such as dimethyl carbonate and diethyl carbonate with low viscosity and low dielectric constant and used in a suitable ratio, an electrolyte with high conductivity can be prepared, so such a combination can be more preferred.
[0170] As the metal salt, a lithium salt can be used. The lithium salt is a material that can be easily dissolved in the non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0171] For the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, improving the discharge capacity of the battery, etc., the electrolyte, in addition to containing the above-mentioned electrolyte components, may further include one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0172] An exemplary embodiment of the present specification provides a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include the secondary battery having high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0173] Example
[0174] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be clear to those skilled in the art that these embodiments are only provided to illustrate the present invention, and various modifications and changes are possible within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims included herein.
[0175] Preparation Example. Preparation of transfer laminate
[0176] Preparation Example 1
[0177] A film (manufacturer: I-ONE Film Co., Ltd.) in which a 1 μm thick acrylic resin film as a release layer was coated on polyethylene terephthalate as a substrate layer was prepared. Lithium metal was deposited on the release layer by thermal evaporation to form a lithium metal layer having a thickness described in Table 1 below, thereby preparing a transfer laminate. In this case, EWK-060 obtained from ULVAC, Inc. was used as a deposition apparatus, and the deposition process was performed under the following conditions: a speed of 2.5 m / min, a temperature of a lithium supply unit of 500° C., and a temperature of a main roller of −25° C.
[0178] Example. Surface treatment of transfer laminates
[0179] Example 1
[0180] Each transfer laminate (Li film, Li thickness 3 μm) prepared as described above was placed in a chamber, which was then placed at 10 -3 Then, the vacuum valve was closed, and the gas purge valve was opened to introduce argon (gas) and carbon dioxide (gas) in a ratio of 8:2 into the chamber at room temperature.
[0181] Each gas was purged until the vacuum level in the chamber reached normal pressure, and after 30 minutes of treatment, the surface color difference of the lithium metal layer (film) was analyzed using CM-2600d.
[0182] The transfer laminate (Li film) after the surface treatment was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion by using a calendaring device under a load of about 200 kgf.
[0183] Example 2
[0184] The same procedure as in Example 1 was performed except that the Li thickness (thickness of the lithium metal layer) of the transfer laminate used was set to 4 μm.
[0185] Example 3
[0186] The same procedure as in Example 1 was performed except that the Li thickness of the transfer laminate used was set to 5 μm.
[0187] Example 4
[0188] The same procedure as in Example 1 was performed except that the Li thickness of the transfer laminate used was set to 6 μm.
[0189] Example 5
[0190] Each transfer laminate (Li film, Li thickness 6 μm) prepared as described above was placed in a chamber, which was then placed at 10 -3 Then, the vacuum valve was closed, and the gas purge valve was opened to introduce argon (gas) and carbon dioxide (gas) in a ratio of 8:2 into the chamber at room temperature.
[0191] Each gas was purged until the vacuum level in the chamber reached normal pressure, and then the temperature in the chamber was maintained at 60° C. After the gas treatment for 5 hours, the surface color difference of the lithium metal layer was analyzed using CM-2600d.
[0192] The transfer laminate (Li film) after the surface treatment was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion by using a calendaring device under a load of about 200 kgf.
[0193] Example 6
[0194] The same procedure as in Example 5 was performed except that the gas treatment was performed for about 24 hours.
[0195] Example 7
[0196] The same procedure as in Example 5 was performed except that the gas treatment was performed for about 12 hours.
[0197] Example 8
[0198] The same procedure as in Example 1 was performed except that the Li thickness of the transfer laminate used was set to 9 μm.
[0199] Comparative Example 1
[0200] The surface color difference of the lithium metal layer of the transfer laminate (Li thickness: 6 μm) produced in Preparation Example 1 was analyzed using CM-2600d without additional gas purging.
[0201] The surface-treated transfer laminate (Li film-lithium metal layer) was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion using a calendaring device under a load of about 200 kgf. In this case, the size of the electrode used for transfer was 5 cm×5 cm.
[0202] Comparative Example 2
[0203] Each transfer laminate (Li film, Li thickness 6 μm) prepared as described above was placed in a chamber, which was then placed at 10 -3 Then, the vacuum valve was closed, the gas purge valve was opened, and each gas was purged with CDA (clean dry air, dew point -40°C) at 25°C until the vacuum level in the chamber reached normal pressure, and then the temperature in the chamber was maintained at 25°C. After 30 minutes of gas treatment, the surface color difference of the lithium metal layer was analyzed using CM-2600d.
[0204] The surface-treated transfer laminate (Li film-lithium metal layer) was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion using a calendaring device under a load of about 200 kgf. In this case, the size of the electrode used for transfer was 5 cm×5 cm.
[0205] Comparative Example 3
[0206] Each transfer laminate (Li film, Li thickness 6 μm) prepared as described above was placed in a chamber, which was then placed at 10 -3 Then, the vacuum valve was closed, and the gas purge valve was opened to introduce argon (gas) and carbon dioxide (gas) at a ratio of 99:1 into the chamber at 25°C.
[0207] Each gas was purged until the vacuum level in the chamber reached normal pressure, and then the temperature in the chamber was maintained at 25° C. After the gas treatment for 30 minutes, the surface color difference of the lithium metal layer was analyzed using CM-2600d.
[0208] The surface-treated transfer laminate (Li film) was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion using a calendaring device under a load of about 200 kgf. In this case, the size of the electrode used for transfer was 5 cm×5 cm.
[0209] Comparative Example 4
[0210] Each transfer laminate (Li film, Li thickness 6 μm) prepared as described above was placed in a chamber, which was then placed at 10 -3 Then, the vacuum valve was closed, and the gas purge valve was opened to introduce argon (gas) and carbon dioxide (gas) at a ratio of 8:2 into the chamber at 25°C.
[0211] Each gas was purged until the vacuum level in the chamber reached normal pressure, and then the temperature in the chamber was maintained at 10° C. After the gas treatment for 30 minutes, the surface color difference of the lithium metal layer was analyzed using CM-2600d.
[0212] The surface-treated transfer laminate (Li film) was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion using a calendaring device under a load of about 200 kgf. In this case, the size of the electrode used for transfer was 5 cm×5 cm.
[0213] Comparative Example 5
[0214] Each transfer laminate (Li film, Li thickness 6 μm) prepared as described above was placed in a chamber, which was then placed at 10 -3 Then, the vacuum valve was closed, and the gas purge valve was opened to introduce argon (gas) and carbon dioxide (gas) at a ratio of 8:2 into the chamber at 25°C.
[0215] Each gas was purged until the vacuum level in the chamber reached normal pressure, and then the temperature in the chamber was maintained at 25° C. After the gas treatment for 3 minutes, the surface color difference of the lithium metal layer was analyzed using CM-2600d.
[0216] The surface-treated transfer laminate (Li film) was attached to both surfaces of the silicon negative electrode, and then lithium was transferred to the electrode portion using a calendaring device under a load of about 200 kgf. In this case, the size of the electrode used for transfer was 5 cm×5 cm.
[0217] [Measurement of fever temperature]
[0218] The heat generation temperatures of the electrodes of Examples 1 to 8 and Comparative Examples 1 to 5 were measured in the following manner: PET was removed immediately after Li was transferred to the electrode portion, and a TC (thermocouple) was attached to the center of the electrode surface to which Li was transferred to measure the maximum temperature value of the heat generating electrode surface.
[0219] The results of Examples 1 to 8 and Comparative Examples 1 to 5 are shown in Table 1 below.
[0220]
[0221] In Table 1 above, CDA refers to the same composition as normal air.
[0222] According to Table 1, in the case of Comparative Examples 1 to 5, it can be confirmed that even when the luminance (L) measured in the SCI mode is 90 or more, the luminance (L) measured in the SCE mode is less than 40, and therefore the heating temperature immediately after the transfer is 38° C. or more.
[0223] On the other hand, in the case of Example 1-8, it was confirmed that the brightness (L) measured in the SCI mode was 90 or more, and the brightness (L) measured in the SCE mode was 40 or more, and therefore the heat generation temperature immediately after the transfer was 30° C. or less.
[0224] Specifically, when the content of carbon dioxide in the surface treatment gas is changed (a trace amount of carbon dioxide is present in CDA, or Ar:CO2 = 99:1) as in the case of Comparative Examples 2 and 3, when the temperature in the chamber is lowered to 10°C after purging the surface treatment gas as in Comparative Example 4, or when the surface treatment time is set to as short as 3 minutes as in Comparative Example 5, the brightness measured in the SCE mode is all less than 40. According to these results, in the embodiment group compared with the comparative example group, even when the surface treatment conditions are changed, it is easy to predict whether lithium carbonate (Li2CO3) is formed in a short period of time, so that the degree of surface treatment can be accurately grasped. As a result, the heat generation temperature immediately after the transfer can be easily predicted, thereby greatly reducing the risk of ignition during pre-lithiation.
Claims
1. A transfer laminate, comprising: a substrate layer; and a lithium metal layer on one surface of the substrate layer, wherein the lithium metal layer comprises a surface protection film on the surface of the lithium metal layer, wherein the surface protection film comprises lithium carbonate (Li2CO3), and The surface color difference of the surface of the lithium metal layer including the surface protection film satisfies the following formula (1): L SCE ≥ 40 Formula (1) In the above formula (1), L SCE Refers to the brightness index measured in the Specular Component Excluded (SCE) mode.
2. The transfer laminate according to claim 1, wherein the surface color difference for the surface of the lithium metal layer including the surface protection film satisfies the following formula (2): L SCI ≥ 90 Formula (2) In the above formula (2), L SCI Refers to the brightness index measured in the Specular Component Including (SCI) mode.
3. The transfer laminate according to claim 1, wherein the surface of the lithium metal layer further comprises one or more components selected from the group consisting of LiOH, Li3N, Li2O, Li2O2 and combinations thereof. The transfer laminate according to claim 1 , wherein the base material layer has a thickness of 5 μm or more and 300 μm or less.
5. The transfer laminate according to claim 1, wherein the substrate layer is one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene and polycarbonate. 6 . The transfer laminate according to claim 1 , wherein the lithium metal layer has a thickness of 1 μm or more and 10 μm or less. 7 . The transfer laminate according to claim 1 , further comprising a release layer between the substrate layer and the lithium metal layer. 8 . The transfer laminate according to claim 7 , wherein the release layer has a thickness of 0.1 μm or more and 10 μm or less.
9. A method for manufacturing a negative electrode for a lithium secondary battery, the method comprising: preparing a negative electrode for a lithium secondary battery by forming a negative electrode collector layer and a negative electrode active material layer on one surface or both surfaces of the negative electrode collector layer; and The lithium metal layer is transferred by laminating the transfer laminate according to any one of claims 1 to 8 onto the surface of the negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer.
10. The method according to claim 9, wherein the transferring the lithium metal layer by laminating the transfer laminate onto a surface of the negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer comprises: laminating the transfer laminate so that a surface of the lithium metal layer opposite to a surface in contact with the substrate layer contacts a surface of the negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer, and The substrate layer is removed.
11. The method according to claim 9, wherein the lamination is performed under a load of 200 kgf.
12. The method according to claim 9, further comprising pre-lithiating the negative electrode active material layer after transferring the lithium metal layer, in, In pre-lithiating the negative electrode active material layer, the negative electrode active material layer is pre-lithiated within 30 minutes to 48 hours after transferring the lithium metal. 13 . A negative electrode for a lithium secondary battery, produced by the method for producing a negative electrode for a lithium secondary battery according to claim 9 .
14. A lithium secondary battery, comprising: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and Electrolytes, One of the first electrode and the second electrode comprises the negative electrode for a lithium secondary battery according to claim 13 .
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A